2018
DOI: 10.1136/tobaccocontrol-2018-054296
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of industry data on pulmonary and immunosuppressive effects of IQOS

Abstract: IntroductionHeated tobacco products are being touted as novel reduced-harm tobacco products by tobacco companies. In the USA, Philip Morris International submitted a modified risk tobacco product (MRTP) application to the US Food and Drug Administration in 2016 in which it purports that its heated tobacco product, I-Quit-Ordinary-Smoking (IQOS), is associated with reduced harm compared with conventional cigarettes.MethodsWe reviewed Philip Morris International’s MRTP application to assess the pulmonary and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 17 publications
2
51
0
5
Order By: Relevance
“…Several of the other papers in this supplement indicate that IQOS is not significantly less harmful than combusted cigarettes 2 4 46 47 and that while IQOS had lower levels of pulmonary cytotoxicity 48 and carcinogens 49 than combusted cigarettes, they were higher than those of e-cigarettes. Therefore, the limited evidence on the health risks of HTPs does not support the much lower levels of perceived harm that PMI’s consumer studies found.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Several of the other papers in this supplement indicate that IQOS is not significantly less harmful than combusted cigarettes 2 4 46 47 and that while IQOS had lower levels of pulmonary cytotoxicity 48 and carcinogens 49 than combusted cigarettes, they were higher than those of e-cigarettes. Therefore, the limited evidence on the health risks of HTPs does not support the much lower levels of perceived harm that PMI’s consumer studies found.…”
Section: Resultsmentioning
confidence: 95%
“…PMI’s MRTP application for IQOS makes reduced risk claims about IQOS that, like its earlier ‘light’ and ‘mild’ claims that were deemed fraudulent in the RICO case, are not substantiated by PMI’s own internal research reported in its application 2 4 . Several of the other papers in this supplement indicate that IQOS is not significantly less harmful than combusted cigarettes 2 4 46 47 and that while IQOS had lower levels of pulmonary cytotoxicity 48 and carcinogens 49 than combusted cigarettes, they were higher than those of e-cigarettes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emerging science indicated that HTP are unlikely to be any ‘healthier’ than conventional cigarettes, including scientific data submitted by PMI as part of its MRTP application to the FDA 8 , 10 , 74 – 77 . The industry’s claims are often speculative, emphasising the ‘potential’ for these new products to either reduce harm or reduce risk of tobacco use 78 , 79 .…”
Section: Discussionmentioning
confidence: 99%
“…The application to sell in the USA without these claims falls under a different process 7 . In particular, despite evidence to the contrary in their MRTP application, 8 10 PMI claimed that smokers who switch completely to IQOS would experience a reduction in the health-related risks associated with smoking 11 , 12 . In January 2018, the FDA Tobacco Product Scientific Advisory Committee recommended against FDA approval of reduced risk claims for IQOS 13 .…”
Section: Introductionmentioning
confidence: 99%